Fiber optic soil water content sensor for precision farming. (May 2022) - Leone, M.; Consales, M.; Passeggio, G.; Buontempo, S.; Zaraket, H.; Youssef, A.; Persiano, G.V.; Cutolo, A.; Cusano, A.
Highlights: Fiber optic sensor for monitoring of soil water content for precision agriculture. Optical fiber technology using a nanoporous ceramic disc to detect soil water content. The sensing platform extremely suitable for monitoring over large areas. Several application fields as smart farming or rainfall-induced landslides monitoring. Abstract: In this work, we propose a novel and cost effective fiber optic platform for the continuous monitoring of soil water content to be exploited in the agri-food sector and, in particular, in the field of precision agriculture to promote the rational use of water resources. The proposed platform arises from the judicious connection of optical fiber technology and functional materials able to exhibit a change in their optical properties depending on the water content in the environment. Al2 O3 disks have been used as functional materials, taking advantage of their capability to absorb water and exhibit a correlated absorbance increase in the wavelength range corresponding to the absorption peak of water. A detailed study has been carried out to obtain the best coupling conditions between optical fibers and the functional disk. The final prototype has been tested directly in soil and the collected results show its capability to detect soil water content variation in the range 0–35% of volumetric water content (VWC) with a sensitivity of 2.3%/%VWC and a VWC resolution lower than 1%. Such performances allow the proposed device to be used for soil water content measurements for applications in several fields and in different hydrogeological conditions, such as, e.g., in smart farming applications, to support farmers in defining a correct irrigation strategy, or for the real-time monitoring of hydrogeological hazard, to prevent rainfall-induced landslide. Moreover, thanks to the capability of optical fibers technology to multiplex different fiber probes while sharing the same interrogation equipment, the proposed platform is endowed with multiplexing capabilities and presents a solid basis for a continuous monitoring of soil moisture monitoring over large areas.